EDUKASI DAN PRAKTIK KOMPOSTING RUMAH TANGGA UNTUK MENCEGAH PEYAKIT BERBASIS LINGKUNGAN: PEMBERDAYAAN DI DESA MONCONGLOE, MAROS, SULAWESI SELATAN - Rahman, Harpiana; Ernasari, Ernasari; Burhan, Zulkhair; Rahman, Haryudi; Septiyanti, Septiyanti (Jurnal Abdi Insani, 2025)
Moncongloe Village is a buffer village facing waste management challenges, such as limited infrastructure and suboptimal public awareness regarding household waste management, which causes the accumulation of garbage on the main village road. This condition has led to environmentally-based infectious diseases such as diarrhea, acute respiratory infections , and dengue fever, among the top 10 diseases recorded by the Moncongloe Community Health Center. This waste accumulation primarily consists of unsorted and unprocessed organic and inorganic waste. To increase the empowerment and participation of Moncongloe Village residents in environmental health efforts, empowerment activities take the form of education related to improving community knowledge and skills in waste management, which can be a strategic solution in efforts to prevent environmentally based diseases. The implementation method used a community group empowerment strategy consisting of several structured stages involving a participatory approach in each stage, namely the problem identification stage, the health education stage through two-way counseling, and the process evaluation stage. This activity successfully increased community knowledge about the importance of household waste management in preventing the transmission of environmentally based diseases. This activity proves that an educational and participatory approach based on community needs and problems effectively encourages changes in community behavior towards a cleaner and healthier environment.